TAX KNOWLEDGE AND TAX MORALE IN TAX COMPLIANCE - Fitri, Fitri; Nurlaela, Nurlaela; Chair, Ummul (LPPM STIE Muhammadiah Bandung, 2022)
This study purpose to find the effect of tax knowledge on tax compliance, the effect of tax morale on tax compliance and find tax morale as a moderating variable that can strengthen the relationship between tax knowledge and tax compliance. This study uses a survey method with a quantitative approach. Questionnaires have been distributed to 127 respondents from 500 target questionnaires distributed. Questionnaire data were analyzed using regression analysis techniques. The results showed that tax knowledge and tax morale had a positive and significant effect on tax compliance. Tax morale also plays a significant role as a moderating variable that strengthens the relationship between tax knowledge and tax compliance. therefore, tax morale needs to be embedded in the education process.